Civil society in times of change: Shrinking, changing and expanding spaces and the need for new regulatory approaches - Helmut K. Anheier; Markus Lang; Stefan Toepler (Kiel Institute for the World Economy (IfW), 2018)
The relationship between many G20 governments and organized civil society has become more complex, laden with tensions, and such that both have to find more optimal modes of engagement. In some instances, state-civil society relations have worsened, leading some experts and activists to speak of a "shrinking space" for civil society. How wide- spread is this phenomenon? Are these more isolated occurrences or indeed part of a more general development? How can countries achieve and maintain an enabling environment for civil society? The authors suggest that much of the current impasse results foremost from outdated and increasingly ill-suited regulatory frameworks that fail to accommodate a much more diverse and expanded set of civil society organizations (CSO). In response, they propose a differentiated model for a regulatory framework based on functional roles. Based on quantitative profiling and expert surveys, moreover, the paper also derives initial recommendations on how governments and civil society could find ways to relate to each other in both national and multilateral contexts.
http://dx.doi.org/10.7910/DVN/FQEMZU
Keywords: F5; L31; H7; K33; 330; civil society; NGOs; Closing Civic Space; nonprofit regulation; G20